KAJIAN ETNOFARMAKOLOGI SUKU MARAE TERHADAP PENGOBATAN TRADISIONALDI DESA KEWAR KECAMATAN LAMAKNEN KABUPATEN BELU - Ni Nyoman Yuliani; Maria Hilaria; Elisma Elisma; Jefrin Sambara (Universitas Islam Negeri Alauddin Makassar, 2019)
Ethnopharmacology is a part of ethnobotany that studies specifically the use of plants for treatment by certain traditional ethnic groups/communities. Ethnopharmacology becomes the spearhead in the search for new active components/substances present in plants. While ethnopharmacology studies are studies of the use of plants that function as medicines or herbs produced by local residents for treatment. The tribe studied in this study is the Marae tribe, which examines the traditional herbs or herbs used by the Marae tribe in treating the illness, this type of research is a descriptive research and using a sampling technique that is purposive sampling. This research was conducted in an interview. The results of this study found 29 types of traditional medicinal plants used by the Marae tribe society in traditional medicine. Many traditional plants have the same regional name as Indonesia, and the most common use of plants is leaves with a percentage (38%), compared to others namely, bark (28%), fruit (24%), rhizome (6%), and interest (4%) the way of utilization used by Marae tribe society including boiling (72%), pounding (17%), chewing (7%), and smeared (4%). The properties of the plants used are high blood pressure, broken bones, diabetes, malaria, ulcers, vomiting blood, bleeding, appendicitis and lungs